Analysis and countermeasures of early delamination of the nitrided tappet insterts in the valve train of a high speed and heavy load diesel engine. (August 2022) - Wang, Guanghong; Zou, Wei; Wu, Beibei; Wu, Pingping; Wu, Han; Chen, Pengfei; Cui, Bin; He, Guangwei; Cai, Ruimou; Qu, Shengguan
Highlights: Occurrence of flying off of tappet caused impact forces between tappet and cam. Weak adhesion and brittleness of CL were responsible for the early delamination. The nitrided tappet inserts with its CL removed was an effective countermeasure. CL of nitrieded parts should be grinded off under a heavy load with impact forces. Abstract: Early delamination of the nitrided tappet inserts in the valve train of a high speed and heavy duty diesel engine occurred and thus the failure mechanism of early delamination was investigated with the method of numerical simulation and experiment at first. Additionally, the countermeasure was put forward and identified using a valve train bench test rig. Flying off of the tappet in valve train took place, causing repeated impact forces between the interfaces of the tappet and cam. Early delamination of the compound layer (CL) was formed once the surface crack connected with the subsurface crack. Removal of the CL of the nitrided tappet inserts was verified as an effective countermeasure for avoiding the early delamination as well as protecting the matching part, which suggests the hard and brittle CL of the nitrided part should be removed under a heavy load condition especially accompanying with repeated impact forces.